Printed wideband antenna with chip-capacitor-loaded inductive strip for lte/Gsm/Umts wwan wireless usb dongle applications - Ban, Yongling (2014)
This paper proposes a planar printed wideband antenna for eight-band LTE/GSM/UMTS WWAN wireless USB dongle applications. An inductive shorted strip with a chip capacitor loaded is employed in order to improve the characteristics of small-size terminal antennas which usually have a narrow band over the LTE700/GSM850/900 (698-960 MHz) operation. While the desired upper band is mainly realized by the rectangular radiating patch, covering DCS1800/PCS1900/UMTS2100/LTE2300/2500 (1710-2690 MHz) band. Easily printed on a 0.8-mm thick FR4 dielectric substrate of size 20×70 mm², the proposed antenna structure occupies a compact size of 20×19 mm². Then the proposed design can be attached to laptop computer by the USB interface. Good radiation efficiency and antenna gain for frequencies over the desired operating bands is obtained. Detailed design considerations of the proposed antenna are described, and both experimental and simulation results are also presented and discussed.